Osseointegration of 3D porous and solid Ti–6Al–4V implants - Narrow gap push-out testing and experimental setup considerations. (March 2021) - Frosch, Stephan; Nüsse, Verena; Frosch, Karl-Heinz; Lehmann, Wolfgang; Buchhorn, Gottfried
Abstract: Porosity in titanium alloy materials improves the bony integration and mechanical properties of implants. In certain areas of application such as vertebral spacers or trabecular bone replacement (e.g. wedge augmentation in prosthetics), surface structures are desirable that promote bone integration and have biomechanical properties that are resistant to intraosseous load transfers and at the same time resemble the stiffness of bone to possible reduce the risk of stress shielding. In the present study, we investigated the biomechanical push-out behavior of an open-porous Ti–6Al–4V material that was produced in a space-holder and sintering method creating a 3-D through-pores trabecular design that corresponds with the inhomogeneity and size relationships of trabecular bone. The short-term and mid-term effects of the material properties on osseointegration in a biomechanical push-out study were compared to those of to a conventional solid Ti–6Al–4V material. In order to raise the measurement accuracy we implemented a strict study protocol. Pairs of cylindrical implants with a porosity of 49% and an average pore diameter of 400 μm and equal sized solid, corundum blasted devices as reference were bilaterally implanted press fit in the lateral femoral condyles of 14 rabbits. After sacrifice at 4 and 12 weeks, a push-out test was performed while the test set-up was designed to ensure conformity of implant axes and direction of applied force. Maximum holding force, Young's modulus, and mode of failure were recorded. Results of maximum push-out force (F-max) revealed a significant material effect (p < 0.05) in favor of porous implants after 4 weeks of osseohealing (6.39 vs. 3.36 N/mm 2 ) as well as after 12 weeks of osseoremodeling (7.58 vs. 4.99 N/mm 2 ). Evaluation of the failure mode resulted in three different types of displacement characteristics, which revealed a different mechanism of osseous anchoring between the two types of implants and substantiate the F-max and Young's modulus results. Conclusively, the porous implant offers surface properties that significantly improve its osseous stability compared to solid material under experimental conditions. In addition, we have optimized our study protocol for biomechanical push-out tests to produce precise and comparable results.